2019
DOI: 10.11648/j.ajmcm.20190403.11
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Forecasting Using ant Colony Optimization Based Algorithm

Abstract: Due to the importance of forecasting the capital market earnings in finance, recently the aspect of stock market prediction has been a major research area that has generated a lot of attention involving various machine learning algorithms. In the recent presentations, it has been indicated that neural networks have some drawbacks in learning the data patterns or that they may perform inconsistently and unpredictable because of the complexity of the stock market data. However, due to the distributive nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…e authors also analysed some classical algorithms and concluded that ACO had outperformed all the other algorithms concerning time series and robustness. From the previous studies, it can be observed that Ant Colony Optimization (ACO) provides better performance when compared to other optimization algorithms [5]. In [6], long short term memory (LSTM) neural networks and long short term memory (LSTM) neural networks with embedded layer (ELSTM) are proposed, discussed, and analysed.…”
Section: Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…e authors also analysed some classical algorithms and concluded that ACO had outperformed all the other algorithms concerning time series and robustness. From the previous studies, it can be observed that Ant Colony Optimization (ACO) provides better performance when compared to other optimization algorithms [5]. In [6], long short term memory (LSTM) neural networks and long short term memory (LSTM) neural networks with embedded layer (ELSTM) are proposed, discussed, and analysed.…”
Section: Related Studiesmentioning
confidence: 99%
“…In [8], the authors tried to predict the corporate financial crisis rather than the numerical financial ratios. e authors of [5] have created a hybrid algorithm for stock market prediction. In their model, the ACO algorithm is implemented using the selection-based model.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical analysis indicators, which are often used with the aim of making short-term gains, may be used to manage complicated data with non-linear correlations. Adhering to these recommendations does not need expert financial knowledge or exploring other marketplaces [5]. There are supplemental charts and mathematical functions known as indicators, which are used to offer indications for buying and selling prices.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, algoritmos de inteligência de enxame têm sido adotados na modelagem baseada em agentes, como Particle Swarm Optimization (Hitam et al, 2019), Ant Colony Optimization (Ahmed et al, 2019), Firefly (Tang et al, 2017) e Cuckoo Search (Lajevardy et al, 2017), entre outros. Tais algoritmos são inspirados em padrões complexos observados na natureza para a elaboração de sistemas computacionais (Serapião, 2017).…”
Section: Introductionunclassified